2002
DOI: 10.1046/j.1523-5394.2002.104003.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Counseling and Programming Preferences of Cancer Survivors

Abstract: The results of this study indicate that cancer survivors have unique and varied exercise counseling and programming preferences. Fifty-six percent of cancer survivors preferred to exercise at moderate intensity rather than at high intensity. Moderate-intensity exercise has been shown previously to be relatively safe even for cancer survivors who are advanced in age. The key to success for inactive cancer survivors may be to provide reassurance that exercise is a safe and beneficial modality for cancer survivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
278
19
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 234 publications
(342 citation statements)
references
References 44 publications
43
278
19
2
Order By: Relevance
“…. Perceived benefits and barriers to exercise were assessed using an adapted Exercise Benefits and Barriers Scale incorporating barriers identified in the literature to be specific to breast cancer patients [11,20,23,26], and the inclusion of a question regarding exercise bra comfort.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…. Perceived benefits and barriers to exercise were assessed using an adapted Exercise Benefits and Barriers Scale incorporating barriers identified in the literature to be specific to breast cancer patients [11,20,23,26], and the inclusion of a question regarding exercise bra comfort.…”
Section: Instrumentmentioning
confidence: 99%
“…No study was located which indicated the adherence rates of exercise among breast cancer patients outside of a research-generated exercise program. Some research exploring exercise adherence and motivation issues in breast cancer survivors has suggested that the strongest correlates of exercise adherence in cancer survivors are not demographic, socio-economic or medical variables but, rather, are social, cognitive variables such as attitudes, perceptions of control and subjective norms [18,[20][21]. Other research also indicates that over half of the barriers to supervised exercise can be directly attributed to the breast cancer disease and treatment [22].…”
Section: Introductionmentioning
confidence: 99%
“…Broad-reaching and low intensive interventions designed to increase PA in breast cancer patients undergoing chemotherapy are warranted. This contention is substantiated by the evidence suggesting that breast cancer survivors indicate that they are interested in pursuing PA and receiving PA counseling and information during their treatments (10,11). Moreover, researchers have contended that the initial treatment period may function as a "teachable moment" in which breast cancer survivors' motivation for lifestyle change may be especially high (10,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer survivors clearly experience a marked decline in PA due to treatment, and this effect persists after treatment has ended [39]; around 16%-20% of all cancer survivors engage in regular PA [40]. Physical fitness is known to affect PA and this association has been investigated in cancer survivors.…”
Section: Effects Of Physical Activity For Cancer Survivorsmentioning
confidence: 99%
“…In that research, cancer survivors showed interest in information about PA. Furthermore, several factors have been identified as determining preference for and interest in such a program including age, current level of PA, educational history, income, obesity, stage of cancer, time elapsed since diagnosis, type of treatment, and comorbidity [40,68,[73][74][75][76]. Other factors are self-efficacy, enjoyment of PA, social support, sensory disturbance, depression, and fatigue [75,77].…”
Section: Determinants Of Physical Activity In Cancer Survivorsmentioning
confidence: 99%